Does geothermal energy and natural resources affect environmental sustainability? Evidence in the lens of sustainable development - Bashir, Muhammad Adnan; Dengfeng, Zhao; Shahzadi, Irum [UNESP]; Bashir, Muhammad Farhan (My University, 2023)
Climate change and global warming have been driven by a rise in carbon dioxide (CO2) concentrations in recent decades, posing a danger to environmental sustainability. Thus, this research scrutinizes the effects of two types of energy (coal and geothermal) and natural resources on CO2 emissions in 10 newly industrialized countries (NICs). The study also considers the role of financial globalization using a data between 1990 and 2019. This research applied a fresh nonparametric econometric technique termed “method of moments quantile regression (MMQR).” This approach is resistant to outliers and produces an asymmetric connection between variables. Furthermore, the long-run estimators (AMG and CCEMG) are employed as a robustness check. The findings reveal that natural resources, coal, and economic growth contribute to the degradation of the environment in the NICs in all quantiles (0.1–0.90). However, geothermal energy aids in enhancing environmental sustainability at all quantile distributions (0.1–0.90). Our findings are robust with alternative methods (AMG and CCEMG). The research’s outcomes have the potential to help NICs nations design policies. Finally, based on the research results, a policy framework is proposed to solve the objectives of SDGs 7 and 13.
Keywords: Coal consumption; Environmental economics; Financial globalization; Geothermal energy; Sustainability